Impact of the COVID-19 lockdown on the economic situation and food security of rural households in India. Issue 3 (7th January 2022) - Suresh, Veena; Fishman, Ram; von Lieres, Johanna Sophie; Rao, Bhavani R.
Abstract : Purpose: The purpose of the study is to understand what impact the first COVID-19 lockdown in 2020 had on the income and food security of rural households in India and whether it differed across socioeconomic factors. Moreover, the study assesses the needs of rural households and determines whether they had received adequate support services during the lockdown. Design/methodology/approach: The study adopted a repeated-measures quantitative survey design with 1, 319 rural women from 16 states of India and conducted a telephonic survey. Findings: The lockdown had directly impacted rural households' employment status and income but the impact differed depending on the type of employment. For example, working in a salaried job or on one's farm led to a lower likelihood of a complete decline in income in states other than Kerala as the lockdown continued. The study also revealed a change in the pattern of food consumption, with higher consumption of subsidized staple foods. It also became evident that the aid announced by the government reached the rural population with some delay. Research limitations/implications: A limitation of the study was that many respondents refused to participate in phase 2, which reduced the sample size when comparing the two phases because the women did not own mobile phones. Instead, they were using their husbands' phones. Originality/value: The study's findings can help better understand the needs of rural populations during crises, such as the COVID-19 pandemic. This can help to plan better and build preventive actions for such populations once their needs are understood. In addition, this can aid disadvantaged people for a minimal level of preparedness and security during such a crisis in the future.